A groundbreaking electrocardiographic observation: “Isoelectric horizontal ST-segment with sharp ST-T angle” a novel sign for acute coronary syndrome - Maitri M. Patel; Sumantkumar G. Patel; Jigar K. Patel; Dhruvkumar M. Patel; Poojan J. Prajapati; Harsh D. Patel; Jayesh S. Prajapati; Lalitkumar B. Patel; Mukundkumar V. Patel (Indian Heart Journal)
Consecutive suspected acute coronary syndrome (ACS) cases were categorized into three groups: Group-1 (ST-depression), Group-2 (T-inversion), and Group-3 (remaining cases). Group-3 was subclassified into isoelectric horizontal ST-segment with sharp ST-T-angle (IHST) positive and IHST negative groups. They underwent serial high-sensitive Troponin-I testing. ACS incidence was 77.96 %, with 33.02 %, 15.96 %, and (15.04 %, 35.96 %) of patients in Groups 1, 2, and 3 (IHST positive, IHST negative), respectively. The presence of IHST exhibited higher sensitivity than T-inversion and greater specificity than ST-depression in detecting ACS. The presence of IHST sign additionally detected 15.04 % of ACS. The presence of IHST was significant among group-3 (p = 0.008) as well as the overall ACS cases (p = 0.048).